2022
DOI: 10.3390/genes13071174
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Key miRNAs and Genes Associated with the Regulation of Non-Small Cell Lung Cancer: A Network-Based Approach

Abstract: Lung cancer is the major cause of cancer-associated deaths across the world in both men and women. Lung cancer consists of two major clinicopathological categories, i.e., small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC). Lack of diagnosis of NSCLC at an early stage in addition to poor prognosis results in ineffective treatment, thus, biomarkers for appropriate diagnosis and exact prognosis of NSCLC need urgent attention. The proposed study aimed to reveal essential microRNAs (miRNAs) involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 114 publications
(154 reference statements)
0
4
0
Order By: Relevance
“…The miRNA expression is speci cally altered in majority of liver diseases (both acute and chronic), thus miRNAs can exert causal roles (being pro-or anti-in ammatory, as well as pro-or anti brotic mediators or being oncogenes as well as tumor suppressor genes) [73]. Investigations have revealed the role of various signature miRNAs in hepatitis viruses, such as, hepatitis B and hepatitis C, by acting as potential biomarkers in its diagnosis and prognosis [74,75] besides diverse diseases, such as sepsis [Ahmad S, Ahmed MM,] and NSCLC [77]. In this context, we identi ed the hub genes associated miRNAs by constructing the mRNA-miRNA construction network.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA expression is speci cally altered in majority of liver diseases (both acute and chronic), thus miRNAs can exert causal roles (being pro-or anti-in ammatory, as well as pro-or anti brotic mediators or being oncogenes as well as tumor suppressor genes) [73]. Investigations have revealed the role of various signature miRNAs in hepatitis viruses, such as, hepatitis B and hepatitis C, by acting as potential biomarkers in its diagnosis and prognosis [74,75] besides diverse diseases, such as sepsis [Ahmad S, Ahmed MM,] and NSCLC [77]. In this context, we identi ed the hub genes associated miRNAs by constructing the mRNA-miRNA construction network.…”
Section: Discussionmentioning
confidence: 99%
“…To predict target miRNAs associated with SIGLEC12 , we employed three databases. (1) TargetScan ( https://www.targetscan.org/vert_80/ accessed on September 08, 2023), this algorithm predicts miRNA targets across multiple genomes [ 26 , 27 ]. miRWalk ( http://mirwalk.umm.uni-heidelberg.de , accessed on September 08, 2023), is a Perl-based system that uses computational approach to predict target sites [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Using the Kaplan–Meier plotter (KM plotter) ( https://kmplot.com/analysis accessed on January 04, 2023), [ 26 , 27 ] to explore the prognostic significance of SIGLEC12 expression in different subtypes of RC. Furthermore, we conducted an analysis of the mutation burden and macrophage effect in the overall survival (OS) of patients, considering specific categories as part of the restricted analysis subtypes.…”
Section: Methodsmentioning
confidence: 99%
“…A very recent study that utilized gene ontology and enrichment analysis in examining miRNA sequencing data from NSCLC tumors showed that CPEB3 was a significantly downregulated protein compared to healthy lung. 113 Identifying strategies to reactivate this protein thus could be a promising strategy for targeting c-Myc in lung cancer. In addition to proteins that bind the 3′UTR, there are proteins that bind to coding sequences of mRNA, called coding region instability-binding proteins (CRI-BPs), which act to protect mRNA from endonuclease activity.…”
Section: Therapeutic Targeting Of C-myc In Nsclc and Sclcmentioning
confidence: 99%